Soil-Transmitted Helminthiasis, Nutritional Status, and Hemoglobin Levels of School-Age Children in Makassar - Fattah, Nurfachanti; Nurmadilla, Nesyana; Irmayanti, Irmayanti; Safitri, Asrini (Green Medical Journal, 2021)
Introduction: Soil-transmitted helminthiasis (STH) is common in areas with poor sanitation. In Indonesia, the prevalence of the disease is still high ranging from 16–72%, despite the elimination efforts that have been done. This study aimed to determine the prevalence of STH, nutritional status, and hemoglobin levels of elementary school-age children in of slum area in Makassar. Methods: This was an observational study with a cross-sectional approach. Subjects were 33 elementary school-age children in one of the slum areas in Makassar, South Sulawesi, Indonesia. Stool samples were collected and examined using the Kato-Katz method. Hemoglobin levels were examined with the Azidemet hemoglobin method using capillary blood samples. Assessment of nutritional status was carried out anthropometrically using weight for height, height for age, and body mass index (BMI) for age as indicators. Results: The prevalence of STH in this study was 27%, all of them had low nutritional status. As many as 15% and 45% of subjects were severely wasted and wasted, respectively, based on the weight for height indication, 61% were wasted based on the BMI for age indicator, and 12% were stunted based on the height for age indicator. Ten percent of the subjects had low hemoglobin levels, none of them had STH. Conclusion: The STH prevalence of school-age children in one of the slum areas in Makassar is still high. Subjects with STH also experienced low nutritional status.